Cardiotoxicity Potential of Loxosceles intermedia Venom in Cavia porcelus - Bretas Ullmann Fernandes , Paula; da Silva Ferreira , Raquel; Dias Araújo, Matheus; Braga Costa dos Santos , Lucas; Raboch Lempek, Marthin; Alves da Silva , Laice; Chavez-Olórtegui , Carlos Delfin; Lima Santos , Renato; Machado Botelho , Ana Flávia; Melo, Marília Martins (Acta Scientiae Veterinariae, 2026)
Background: Bites from spiders of the genus Loxosceles, popularly known as the brown recluse spider, can cause a syndrome called loxoscelism, which is classified into cutaneous and viscerocutaneous forms. The cutaneous form, which is more common, causes the development of a necrotizing lesion with gravitational spread at the bite site. The viscerocutaneous form, which is rarer, includes systemic symptoms such as intravascular hemolysis, thrombocytopenia, and acute kidney injury, which can lead to death. However, clinical reports suggest a potential cardiotoxic role of Loxosceles venom, although this has been little studied. It should be noted that phospholipase-D is the main toxin present in the venom and has been implicated as the factor responsible for the development of cardiac dysfunction. Given this context, the present study sought to deepen the understanding of the effects of L. intermedia spider venom on the hearts of guinea pigs, using a detailed approach involving cardiac biomarkers, electrocardiograms, and histopathological analysis through optical and electron microscopy. Materials, Methods & Results: Eighteen male guinea pigs (Cavia porcellus) weighing 600 g were used. Of these, 16 animals received intradermal injections of Loxosceles intermedia venom at doses ranging from 11.6 to 350 μg diluted in 0.5 mL of 0.9% saline, and 2 animals received only 0.5 mL of 0.9% saline, serving as controls. Cardiac function was assessed by serial electrocardiograms and by measuring serum cardiac biomarkers, such as creatine kinase (CK) and its MB fraction (CK-MB), lactate dehydrogenase (LDH), troponin I (TnI), N-terminal fragment of B-type natriuretic peptide (NT-ProBNP) and D-dimer at 24 and 72 h post-injection. After 72 h, the animals were euthanized for histopathological and ultrastructural analysis of cardiac tissue using optical and transmission electron microscopy. Survival time varied inversely with the venom dose. Electrocardiograms recorded before envenomation showed no abnormalities. However, after Loxosceles envenomation, ECG changes were observed, including cardiac arrhythmias such as junctional beats and supraventricular extrasystoles, paired ventricular extrasystoles associated with isolated junctional beats, isolated junctional beats and atrioventricular block, junctional arrhythmia, and isolated atrial extrasystole. Elevated CK, CK-MB, LDH, and TnI levels were observed. Histopathological changes included diffuse cardiac congestion and focal hemorrhage, while ultrastructural analysis revealed autophagic vacuoles and mitochondrial damage in cardiac fibers. Discussion: This research was the 1st to conduct a clinical study on systemic loxoscelism and its cardiovascular impacts. The data obtained demonstrate that loxoscelism envenomation can cause significant cardiac and biochemical alterations, with rapidly manifesting effects, such as atrial and ventricular premature beats. Atrial premature beats result from early atrial ectopic beats, and ventricular premature beats present as beats originating early in the ventricle, with a post-extrasystolic pause. In envenomations, ventricular premature beats are associated with damage to cardiac muscle fibers due to myotoxic activity and impaired perfusion of cardiac tissue. Junctional beats, which are early ectopic beats originating in the atrioventricular junction, were also observed. Therefore, these results indicate that loxoscelism venom can directly interfere with cardiac electrophysiology, causing conduction disturbances and arrhythmias. Furthermore, the venom was capable of generating histological lesions consistent with myocardial damage that may also indirectly contribute to impaired cardiac function through mechanisms such as hypoxia and hemorrhages. Keywords: Loxosceles intermedia, loxoscelism, cardiotoxicity, cardiac biomarkers, electrocardiogram.